EFEKTIVITAS PESTISIDA NABATI EKSTRA DAUN IWI (Dioscorea alata L.) UNTUK MENGENDALIKAN HAMA Spodoptera frugiperda PADA TANAMAN JAGUNG - Melyanus Killa, Yonce; Kandokang Madik, Zandrial (Jurnal Biogenerasi, 2025)
Spodoptera frugiperda is one of the most important leaf pests because it has a wide host range including food crops, industrial crops and horticultural crops. First instar larvae damage plants by boring into leaves and eating leaf tissue, leaving transparent marks on the leaf surface. Corn is a food crop that is a substitute for rice which is very important for human needs. In addition, corn also has a very important role as the main raw material in the animal feed industry. This study used the Completely Randomized Design (CRD) method with 5 treatments repeated 4 times, resulting in a total of 20 experimental units. The treatments applied were as follows: k0 = 0% (100 ml of distilled water), k1 = 10% (10 ml of iwi leaf extract + 90 ml of distilled water), K2: 20% (20 ml of iwi leaf extract + 80 ml of distilled water) K3: 30% (30 ml of iwi leaf extract + 70 ml of distilled water). K4: 40% (40 ml of iwi leaf extract + 60 ml of distilled water. The results of this study indicate that the use of iwi leaf extract has no significant effect on armyworm pests. On all observed parameters.